Running the show the essential guide to being a first assistant director - Gill, Liz (Routledge, 2020)
"Whether it's a crew of two hundred shooting a cast of thousands on horseback, or a crew of twelve filming one person in a room, each and every successful movie production requires a strong First Assistant Director (AD) at its helm. In this new and updated edition, veteran First AD Liz Gill walks you through the entire filmmaking process through the perspective of the First AD, from pre-production, shoot, wrap, and everything in between. This book provides invaluable insight into working as a First Assistant Director, featuring tricks-of-the-trade for breaking down a script, creating a schedule and organising test shoots, alongside how to use turnaround time, weather cover, split days, overtime and continuous days to balance a challenging schedule and get the most from the cast, crew, and the shoot. This new edition has been fully updated and expanded throughout to provide up-to-date coverage on new equipment and software, health and safety considerations, and the implications of VFX. This is the essential guide to becoming a successful First Assistant Director, ideal for professional and aspiring AD's seeking to further their career, students of directing and production looking to gain a better understanding of how this department works, and anyone interested in film & TV production. The accompanying e-Resource provides an expanded selection of sample call sheets, report templates, checklists, and other useful documents"--